Idlewild : The Rise, Decline, and Rebirth of a Unique African American Resort Town - Stephens, Ronald Jemal (Book collections on Project MUSE., 2013)
In 1912, white land developers founded Idlewild, an African American resort community in western Michigan. Over the following decades, the town became one of the country's foremost vacation destinations for the black middle class, during its peak drawing tens of thousands of visitors annually and hosting the era's premier entertainers, such as The Four Tops, Della Reese, Brook Benton, and George Kirby. With the civil rights movement and the resulting expansion of recreation options available to African Americans, Idlewild suffered a sharp social and economic decline, and by the early 1980s the town had become a struggling retirement community in the midst of financial and political crises. Unearthing never-before-seen historical material, this book examines the rapid rise and decline of this pivotal landmark in African American and leisure history, in the process exploring intersections among race, class, tourism, entertainment, and historic preservation in the United States. Featuring a wealth of fieldwork on contemporary Idlewild, the book also takes a look at recent revitalization efforts and analyzes the possibilities for a future resurgence of this national treasure.--description provided by publisher.